Uji Aktivitas Ekstrak Etanol Kulit Buah Apel ( Pyrus malus, L) Terhadap - Suparmia, Khusnul Khotimah Amal Fadho (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2013)
Apple (Pyrus malus, L) is a fruit having much uses for health containing phytochemical and flavonoid substances. One of the substances contained in apple rind is quercetin. Quercetin capable to reduce vascular permeability (Mochizuki et al., 2004). The recent study has an aim to know activity of ethanol extract on apple rind to the reducing of vascular permeability thus it can used as therapies for plasma leakage in curing Dengue Blood Fever. The vascular permeability test it was done an induction method using acetate acid. Testing done on white male mice of the BALB/c strain where the mice were divided into 5 groups. The first and second groups were control groups that are a positive control were given 0.2 mg/20 g standard quersetin suspension and the negative one was given 0.5% Na CMC suspension. The third, fourth and fifth groups were treatment groups where each testing animals were given ethanol extract suspension of apple rind by dosages 0.2, 0.4, and 0.8 mg/20 g of Body Weight mice per oral. Taking data was done by measuring pigment intensities from abdominal cavity liquid had been washed with acetate saline. From percentages of vascular permeability reducing each group then analyzed using statistic analyses those were the one-way anova. If there was found any significant difference then it was continued a Tukey test and bivariate-correlation. From results in the study it was known that percentages of vascular permeability reduces of ethanol extract that were made from apple rind having dosages 0.2, 0.4, and 0.8 mg in sequences as big as 42.15%, 63.28% and 84.19%.Keywords: Pyrus malus, L, kuersetin, vascular permeability